2021
DOI: 10.3390/biomedicines9111560
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Variations of 3′UTR Length Reprogram the mRNA Regulatory Landscape

Abstract: This paper concerns 3′-untranslated regions (3′UTRs) of mRNAs, which are non-coding regulatory platforms that control stability, fate and the correct spatiotemporal translation of mRNAs. Many mRNAs have polymorphic 3′UTR regions. Controlling 3′UTR length and sequence facilitates the regulation of the accessibility of functional effectors (RNA binding proteins, miRNAs or other ncRNAs) to 3′UTR functional boxes and motifs and the establishment of different regulatory landscapes for mRNA function. In this context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 235 publications
(232 reference statements)
0
21
0
Order By: Relevance
“…Interestingly, most members of Clusters VI, VII, VIII, and IX contained UTRs. Most members of Clusters VI and VII contained long 5′ UTRs, while most members of Cluster VIII contained long 3′ UTRs, which might be related with their mRNA stability, translation efficiency, and gene expressions [ 29 , 30 , 31 ]. In total, 10 different motifs were identified and shown in Figure 2 , while motifs one, two, and three were the most conservative/common motifs of EjSAURs , as 76 EjSAURs contained these three motifs.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, most members of Clusters VI, VII, VIII, and IX contained UTRs. Most members of Clusters VI and VII contained long 5′ UTRs, while most members of Cluster VIII contained long 3′ UTRs, which might be related with their mRNA stability, translation efficiency, and gene expressions [ 29 , 30 , 31 ]. In total, 10 different motifs were identified and shown in Figure 2 , while motifs one, two, and three were the most conservative/common motifs of EjSAURs , as 76 EjSAURs contained these three motifs.…”
Section: Resultsmentioning
confidence: 99%
“…In general, polymorphisms in the 3‘UTR as well as other variants (e.g., length, regulation by miRNAs, etc.) affect mRNA degradation [ 45 ], and there is also evidence in the literature that common variants of the coding region, even synonymous SNPs, may also alter mRNA stability [ 46 ]. Our assumption is substantiated by an extra hairpin loop predicted in the flanking region of the polymorphic site in the minor variant in silico ( Figure 2 b,c) and confirmed by a hindered mRNA degradation seen after actinomycin D treatment in vitro ( Figure 2 d).…”
Section: Discussionmentioning
confidence: 99%
“…Gene structural diversity may promote protein functional diversity. The CDS contains exons that encode protein sequences, and the UTR is a noncoding region at either end of the mRNA that contains many different regulatory elements involved in variable splicing ( Mayr, 2019 ; Navarro et al, 2021 ). For the gene structures of the families in Cucurbitales involved in the CS pathway, we found that the Cucurbitaceae shows more diversity than Begoniaceae.…”
Section: Discussionmentioning
confidence: 99%